Impact of simplified transcatheter aortic valve implantation approach on procedural and clinical outcomes - Güney, Murat Can (The European Research Journal, 2025)
Objectives: Increased operator experience and development of techniques have reduced complication rates, and the new trend is the simplified approach (SA) in transcatheter aortic valve implantation (TAVI). The aim of this study is to compare the safety, efficacy, and outcomes of the SA with the standard non-simplified approach (NSA). Methods: We retrospectively included 517 consecutive symptomatic severe aortic stenosis (AS) patients undergoing TAVI. The procedure is performed under general anesthesia accompanied by TEE and with predilatation in the NSA group. Whereas sedation and local anesthesia, removal of the routine use of transesophageal echocardiography (TEE), skipping the predilatation step in appropriate patients is adopted in SA group. Results: Among 517 patients, 144 underwent TAVI with SA and 363 with NSA. The NSA group was treated with the most Sapien XT valve (69.4% vs. 92.8; P<0.001). There were no significant differences in post-procedural complications between the groups as defined by the Valve Academic Research Consortium (VARC)-2 criteria. Although there was a trend toward lower mortality at 30-day favoring SA group, this finding did not differ significantly between the groups (0% vs. 2.9%, respectively for SA and NSA groups, P=0.058). However, total cumulative mortality at the end of the follow-up period was found to be significantly reduced in the SA group (7.6% vs. 35.7; P<0.001). The multivariate logistic regression analysis revealed that predilatation, general anesthesia, TEE guidance, and simplified approach were independent predictors of total mortality. Conclusions: Our study showed that simplified TAVI procedure was safe and was no related to adverse events. Compared to the NSA group, SA-TAVI had statistically significant lower total mortality rates.